Role of the HIV-1 Matrix Protein in Gag Intracellular Trafficking and Targeting to the Plasma Membrane for Virus Assembly - Ghanam, Ruba H.; Samal, Alexandra B.; Fernandez, Timothy F.; Saad, Jamil S. (Frontiers in Microbiology, 2012)
Human immunodeficiency virus type-1 (HIV-1) encodes a polypeptide called Gag that is able to form virus-like particles (VLPs) in vitro in the absence of any cellular or viral constituents. During the late phase of the HIV-1 infection, Gag polyproteins are transported to the plasma membrane (PM) for assembly. In the past two decades, in vivo, in vitro and structural studies have shown that Gag trafficking and targeting to the PM are orchestrated events that are dependent on multiple factors including cellular proteins and specific membrane lipids. The matrix (MA) domain of Gag has been the focus of these studies as it appears to be engaged in multiple intracellular interactions that are suggested to be critical for virus assembly and replication. The interaction between Gag and the PM is perhaps the most understood. It is now established that the ultimate localization of Gag on punctate sites on the PM is mediated by specific interactions between the MA domain of Gag and phosphatidylinositol-4,5-bisphosphate (PI(4,5)P2), a minor lipid localized on the inner leaflet of the PM. Structure-based studies revealed that binding of PI(4,5)P2 to MA induces minor conformational changes, leading to exposure of the myristyl (myr) group. Exposure of the myr group is also triggered by binding of calmodulin, enhanced by factors that promote protein self-association like the capsid domain of Gag, and is modulated by pH. Despite the steady progress in defining both the viral and cellular determinants of retroviral assembly and release, Gag’s intracellular interactions and trafficking to its assembly sites in the infected cell are poorly understood. In this review, we summarize the current understanding of the structural and functional role of MA in HIV replication.